The employment consequences of Brexit for seafarers - Gorrochategui Polo, María (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The exit of the United Kingdom from the European Union has had numerous consequences for seafarers, which have not been addressed by the instrument that governs the relationship between the parties, which is the Trade and Cooperation Agreement. The aim of this paper is to analyse the most significant consequences for this group of workers from an employment point of view, focusing specifically in two aspects: the ending of free movement of workers between the UK and the EU and the emergence of fears of unfair social competition as a result of a possible downgrading of seafarers’social conditions.